HUBUNGAN MIGRASI TERHADAP TINGKAT KUALITAS SARANA SANITASI RUMAH TANGGA DI JAKARTA: ANALISIS DATA MIKRO SUSENAS 2017 - Noviyati Valentina Sidabutar; Chotib Chotib (Research Centre for Population, Indonesian Institute of Sciences, 2020)
Jakarta's population is influenced by dynamic population growth regarding high migration flows. Migrants can be a resource in urban development and a burden to the environment concerning population density. For instance, problems of housing provision and basic sanitation services. This study aims to identify the relationship of migration on the quality household sanitation facilities level in Jakarta. This study uses multinomial logistic regression as an analytical method by applying three migration relationships models to the quality level of household sanitation facilities. The source for the analysis is Susenas microdata of 2017. Research findings specifically indicate a significant influence of recent migration on the quality level of household sanitation facilities. It confirmed that migrant households who have stayed longer (migrant lifetime and non-migrant recent) have the opportunity to safe sanitation facilities. Similar opportunities apply to recent migrants with characteristics of older age, higher education, and high expenditure. Conversely, this study found the percentage of households within the lowest category that is identical to the lease housing status with improper living conditions. To reduce the number of the latter category, the local government needs preventive planning in dealing with migration flow. Therefore, migrants can have a comfortable life in the city.